The Journey of Mapping the Entire Destination Lifecycle - Andrianto, Tomy; Kusumah, Ahmad Hudaiby Galih (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2021)
The two destination life cycle models proposed by Plog (1974) and Butler (1980) have been recognizing by most of the tourism destination scholars. Questions tend to arise on the possible use of these models to map the entire destination life cycle from the beginning. Therefore, this study aims to discuss the possibility of entire lifespan of tourism destination by using the destination life cycle models from Plog and Butler. This research analyses the strengths and weaknesses of the models revealed from existing studies using critical inputs of the tourism industry. The main difference between the famous models, i.e. Butler and Plog lies in the authors' background and the approach of the different themes. Complexity factors such as multi-market, time boundaries, political agenda, market evolution/ access, mode of transportation, and technological innovation, makes it impossible to map the entire destination life cycle confidently. The ability to innovate reduces the relevancy of life cycle models. Therefore, the DMO needs to deal with the changes associated with increasing the destination's values to avoid stagnation or decline in stages.